2005
DOI: 10.1115/1.1862260
|View full text |Cite
|
Sign up to set email alerts
|

Peak and Post-Peak Power Aerodynamics from Phase VI NASA Ames Wind Turbine Data

Abstract: Constant speed/pitch rotor operation lacks adequate theory for predicting peak and post-peak power. The objective of this study was to identify and quantify how measured blade element performance characteristics from the Phase VI NASA Ames 24m×36m80ft×120ft wind tunnel test of a two-bladed, tapered, twisted rotor relate to the prediction of peak and post-peak rotor power. The performance prediction code, NREL’s Lifting Surface Prescribed Wake code (LSWT), was used to study the flow physics along the blade. Air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Inadequacies of current simulation methods come in a signifi cant proportion from an incorrect modelling of rotational effects affecting the boundary layer on the turbine blades once the phenomenon of stall is initiated. 1,2 These rotational effects are the cause of the so-called stall delay phenomenon, also refered to as rotational augmentation, which is characterized by signifi cantly increased cone angle, and a global pitch of 3 degrees, defi ned as the angle between the chord at the tip of the blade and the rotational plane. One of the blades was equipped with pressure taps distributed around the airfoil section at 22 different positions, more concentrated near the leading edge of the section to render a better resolution in this more active region of pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequacies of current simulation methods come in a signifi cant proportion from an incorrect modelling of rotational effects affecting the boundary layer on the turbine blades once the phenomenon of stall is initiated. 1,2 These rotational effects are the cause of the so-called stall delay phenomenon, also refered to as rotational augmentation, which is characterized by signifi cantly increased cone angle, and a global pitch of 3 degrees, defi ned as the angle between the chord at the tip of the blade and the rotational plane. One of the blades was equipped with pressure taps distributed around the airfoil section at 22 different positions, more concentrated near the leading edge of the section to render a better resolution in this more active region of pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, this correction is invalid for yawed flow conditions due to the significant impacts of the unsteady shed vorticity and the effects of the skewed wake. Tangler et al [12,13] established an iterative process to derive the angle of attack distributions by a prescribed-wake vortex model and the experimental aerodynamic loads on the NREL rotor under axial flow conditions. The process mainly starts with an initial radial distribution for the angle of attack and, subsequently, the unsteady normal and tangential forces coefficients and the angle of attack are used to determine the lift force coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Lindenburg 7 and Sørensen et al 25 discussed this topic and suggested that future work is necessary to gain better physical understanding. Lindenburg 7 did suggest a decrease in the lift coefficient near the tip, which had also been proposed earlier by Gerber et al 22 However, it is unclear whether or not the commonly observed overprediction of blade tip loads using blade element momentum (BEM)-type methods is rooted in rotational augmentation or due to inaccurate tip correction factors. The work of Madsen et al, 26 for example, proposes novel approaches to tip loss corrections.…”
Section: Blade Rotational Effectsmentioning
confidence: 61%
“…However, the majority of researchers suggest an increase in the drag force on a rotating blade. 7,12,14,[19][20][21][22][23][24] The effect of blade rotation near the blade tip is another area of current research efforts. Lindenburg 7 and Sørensen et al 25 discussed this topic and suggested that future work is necessary to gain better physical understanding.…”
Section: Blade Rotational Effectsmentioning
confidence: 99%